The Implementation of Sharia Nursing Care on Patients' Knowledge, Attitudes, Behavior, and Satisfaction - Edi Yulia Ramdan; Muhammad Hadi; Melati Fajarini; Fitri Arofiati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Patient satisfaction is paramount for healthcare providers, including hospitals. Sharia nursing care is a new paradigm that addresses the need for care based on sharia principles as part of the client’s spiritual aspect. Objectives: To measure the impact of implementing Sharia Nursing Care on patients' knowledge, attitudes, behavior, and satisfaction at Malingping General Hospital, Banten Province. Methods: A quasi-experimental design with a two-group pre-test and post-test approach was conducted in the Tulip and Bougenville wards from February to July 2022, involving 20 patients. A questionnaire was used to collect data on all variables. Data were analyzed using a dependent t-test. Results: There were differences in patients' knowledge, attitudes, behavior, and satisfaction levels before and after the implementation of Sharia Nursing Care in the intervention group. There were also differences in the control group before and after the implementation. Conclusion: The implementation of Sharia Nursing Care had an effect on both the intervention and control groups at Malingping General Hospital.